Efisiensi Teknis Usaha Pengasapan Ikan Cakalang Di Provinsi Sulawesi Utara Dan Faktor-Faktor Yang Mempengaruhinya - Ira Primalasari; Ketut Sukiyono; M Mustopa Romdhon (Agric, 2019)
The research purpose is to determine the technical efficiency level and analyze the factors that influence technical efficiency of the Skipjack smoked fish processing business in North Sulawesi Province. The research method used is survey method in North Sulawesi Province. The data analysis used are descriptive and frontier production function. The production inputs are Skipjack fish, ice cubes, clean water, bamboo clamp, woka leaves, fuel, food coloring and labor. Samping technique with census as many as 81 people. The results show that Skipjack fish and water factors has positive and significant effect on production. The technical efficiency of the Skipjack fish business has an average of 96,17%. Seventy percent of respondent have range of 96-100% technical efficiency. Family size has a positive and significant effect on technical efficiency while age, education and experience have not. Variable of fresh skipjack and water have a significant effect on production, and there is still a 5% chance to increase production by increasing efficiency.